The survey kit.1 : the survey handbook - Fink, Arlene (Thousand Oaks, Calif : Sage Publications, 1995)
This book explains 4 different types of survey instruments, and the activities that constitute a "typical" survey. It also demonstrates how to organize surveys and estimate their costs, and provides details for conducting a survey.
Includes bibliographical references.
Keywords: Surveys -- Methodology; Social sciences -- Statistical methods